Sumber dan Cara Mengatasi Rasa Bersalah pada Wanita Perokok yang Memiliki Anak Balita - Fitri, Rani Agias (Humaniora, 2015)
The objective of this research is to obtain a description of guilty feeling experienced by smoking women who have toddler. Research used qualitative method with interview technique to collect data. There were three subjects in this research who were actively smoking before getting pregnant and currently having toddler. The guilty feeling arises because the subjects realized that smoking behavior is not good and has negative impact to their child. The efforts that subjects do to lessen their guilty feeling are stop smoking and not smoking near their child.